1998
DOI: 10.1097/00007890-199810150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Nuclear Factor-??B Activity and Nitric Oxide Production in Rejecting Cardiac Allografts1

Abstract: These data support a role for NF-kappaB in allograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…Furthermore, spintrapping studies showed definitive evidence that the loss of an atom of Fe in purified aconitase serves as a source of hydroxyl radical formation (30). These findings are interesting considering the previous benefits on graft survival associated with treatment with a hydroxyl radical scavenger, dimethylthiourea, or the metal chelator, pyrrolidine dithiocarbamate (11,31). These studies indicate that the molecular alteration in activity of the native aconitase enzyme with the loss of a reactive metal ion may have a significant affect on cell respiration and production of cell injury.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, spintrapping studies showed definitive evidence that the loss of an atom of Fe in purified aconitase serves as a source of hydroxyl radical formation (30). These findings are interesting considering the previous benefits on graft survival associated with treatment with a hydroxyl radical scavenger, dimethylthiourea, or the metal chelator, pyrrolidine dithiocarbamate (11,31). These studies indicate that the molecular alteration in activity of the native aconitase enzyme with the loss of a reactive metal ion may have a significant affect on cell respiration and production of cell injury.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, in the setting of excess NO production via iNOS, it is possible that molecular interactions of NO with iron-containing proteins may lead to altered cell function or cell injury. Indeed, nitrosylation of heme protein (notably myoglobin) has been demonstrated by EPR spectroscopy in acute cardiac allograft rejection (10)(11)(12). EPR signals for nitrosylated heme protein are found in allograft tissue but not isograft tissue, suggesting that the increase in nitrosylation is due to alloimmune activation rather than secondarily to artifacts of surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the first experiment, pyrrolidine dithiocarbamate, an iron-chelator, prolonged grafts survival and inhibited down-stream effects on nitrosylation of myocardial heme protein [48,49]. While this agent inhibited NF-κB binding activity, it was not determined whether the decreased heme protein nitrosylation was due secondarily to NO scavenging or to decreased iNOS protein expression.…”
Section: Evidence Using No Neutralizing Agentsmentioning
confidence: 99%
“…However, administration of pyrrolidine dithiocarbamate (PDTC), a potent inhibitor of NFkB, markedly prolonged graft survival with a decreased peak of NFkB activity in this model. 15 The immunosuppressive agents FK506 and cyclosporin A (CsA) are reported to switch off gene transcription by inhibiting a key signaling phosphatase, calcinurin, which is involved in the activation of NFkB. [16][17][18] Glucocorticoid, another major immunosuppressive agent, is also believed to work partly via inhibition of NFkB activation.…”
Section: Introductionmentioning
confidence: 99%